TERMS OF USE OF INFORMATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Today, information and communication technologies are developing on a large scale throughout the world. This article talks about the role of information technology in the educational process, the conditions of its use.